Description of Khamul, gen. n. (Hymenoptera: Chalcidoidea: Eurytomidae), with a hypothesis of its phylogenetic placement - Gates, M. W. (Zootaxa, 2008)
Khamul n. gen., a distinctive eurytomid in the subfamily Eurytominae is described from the Neotropics based upon the type species, K. erwini, n. sp. A hypothesis of its phylogenetic placement within Eurytominae is presented, and four new species are described: K. erwini, K. gothmogi, K. lanceolatus, and K. tolkeini. Diagnostic features are included to distincguish this taxon from other eurytomines and a key to species presented. Its biology is unknown, but label data indicate walking stick eggs (Prisopus sp.; Phasmatodea: Prisopodidae) as a possible host.